Research on Sima Chengzhen and His Treatise on the Plain Zither - Wang, Ting (International Journal of Education and Humanities, 2025)
As a Daoist priest, literary scholar, and musician during the flourishing Tang Dynasty, Sima Chengzhen made outstanding contributions to Daoist theory while also achieving profound mastery in musical arts. His work Treatise on the Plain Zither offers a profound exposition of guqin culture, establishing itself as a crucial text for studying Tang Dynasty guqin art. This article examines the subject from three perspectives: Sima Chengzhen's life and character, an analysis of the musical aesthetic philosophy in Su Qin Zhuan, and a comparative study of Su Qin Zhuan with other qin treatises.